Re-reading the Archive: A 21st Century Re-appraisal of Kurosawa’s "The Bad Sleep Well" as a Modern "Hamlet" - van Zon, Stan Reiner (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Among Japanese film director Kurosawa Akira’s three Shakespeare films, Throne of Blood (1957), Ran (1985), and The Bad Sleep Well (1960), the latter has been relatively ignored in Anglophone Shakespeare criticism. This article investigates the Anglophone reception of The Bad Sleep Well and argues in favor of its re-appraisal as a Hamlet. On reception, it examines three explanations for the neglect: its modern setting, its deconstructive adaptation, and its cinematic quality. Considering the latter unconvincing, the article posits that the first two were only detrimental to the film’s reception because they respectively did not conform to Western expectations of essentially pre-modern ‘Oriental’ Japan and of ‘straight’ canonical Shakespeare. Considering changed attitudes in Shakespeare studies, neither of these should still be held against the film. On re-appraisal, The Bad Sleep Well may be reread in the 21st century as part of our continuing memory of our global Shakespeare discourse. Centering on the film’s innovative presentation of Claudius and The Mousetrap, the article argues for the porous border between ‘straight’ production and ‘crooked’ adaptation, and the value to the tradition of oblique approaches to familiar scenes and characters. By arguing for The Bad Sleep Well as a Hamlet worthy of study, the article furthers discussion on archival silences and new rhizomatic models of global Shakespeare that seek to move past the more reductive qualities of the ‘national Shakespeares’ mode of discourse that dominated in the 1990s and 2000s.